WHAT DETERMINES HEALTH? AN AIDE MEMOIRE FOR HEALTH PROFESSIONALS - Shaikh, Babar Tasneem (Journal of Ayub Medical College Abbottabad, 2011)
Health indicators especially in the developing countries have been improving gradually but too slowly to be at par with the Millennium Development Goals closing date. Pakistan in the community of SAARC as well as EMRO countries has been struggling to achieve a decent position vis-Ã -vis the Neonatal Mortality Rate, Infant Mortality Rate, U5Mortality Rate, Maternal Mortality Ratio, Institutional deliveries, Maternal & Child Nutrition, Contraceptive Prevalence Rate, Immunization coverage etc. If analysed critically, all these issues of public health come under the ambit of primary health care. Decades ago, the movement of strengthening primary health care echoed and pledged to consider the local circumstances and available resources to provide essential and appropriate health care at the door steps of the community.1 Tackling these huge challenges, any systems needs evidence base, rational policy decisions and of course that follows just resource allocation and pragmatic approaches to achieve the desired results. Hitherto, the biomedical research somehow has failed to create that needed evidence base and therefore the paradigm shift occurred in the world of health research, globally.2 It has been oft-advocated to employ the innovative research models and adopt new frameworks to study the health seeking behaviours, health seeking patterns and the determinants of health service utilisation, particularly in the developing countries, where the socio-cultural and economic scenario is quite diverse and complex.3 Whether it is the John Snow’s story of Broadway Street in finding the epistemology of cholera or it is the philosophy of Virchow who corelated the incidence of tuberculosis with household economics and the prevailing poverty in the society, the primary determinants of disease are mainly economic and social and therefore its remedies must also be economic and social. The same school of thought eventually is reflected in the millennium declaration where poverty alleviation, improving nutrition, literacy and women empowerment as the mainstay for achieving the MDGs 4, 5 and 6. Reiterating the main agenda, the WHO’s Commission for Social Determinants for Health presented three over-arching recommendations on what needs to be done to reduce health inequities and to close the health gap within and between countries: improve daily living conditions; tackle inequitable distribution of power, money, and resources; and measure and understand the problem and assess the impact of action.4 Today, people of Pakistan are suffering from the worst of poverty: poverty of economics, poverty of literacy and perhaps poverty of imagination. Compounding on to this is the absence of a responsive health system, which cares for dignity and respect of the people and considers health a right of all citizens.5 In this scenario, not having an equitable access to the essential and basic healthcare, makes them vulnerable to severe health shocks. The rural/urban differentials make the picture even more desolated. Prevalence of different categories of shocks (% of all shocks faced by households) Source: Government of Pakistan. Social Protection Strategy, Planning Commission, Islamabad: 2007. In the last 5 years alone, health shocks have emerged to be affecting a large proportion of the population in the country, even more than the natural catastrophes which dismantled the whole agricultural, water, livelihood and public infrastructure. The researchers, managers, policy makers, development partners and the civil society ought to understand that disease focused approach will never deliver results. It has to be a holistic approach underscoring all the social determinants relevant to the context in order to build a responsive and result oriented health system to serve the vulnerable segments of our population.6 This system must be raised on the basic principles of fairness and equity. More we have the social justice in the society, more the health becomes apolitical and accessible as a basic human right. If the picture is to be turned around and reformed, the policies, priorities, programs and interventions must consider socio-cultural dynamics.7 Pakistan is at an important juncture where decentralised form of governance is being instituted. This is undoubtedly a more practical opportunity for health sector (public, non- J Ayub Med Coll Abbottabad 2011;23(3) 2 http://www.ayubmed.edu.pk/JAMC/23-2/Editorial.pdf governmental, donors) to involve other entities such as education, finance, planning, agriculture, women development, water and sanitation, transport, communication and social welfare to shoulder the health agenda at the very local level. Logically, this would be in line with the spirit of Alma Ata Declaration, the Millennium Summit, and the recommendation of Commission for Social Determinants of Health. For Pakistan, this is the perhaps time to refresh its pledges!